Peran Grup WhatsApp sebagai Media Interaksi Sosial Dosen dan Mahasiswa - Febri Nanda Monalisa; Eka Lestari; Eka Susanti; Rismoninta Padang; Saniah Nurhasanah; Sri Andriani (Sublim: Jurnal Pendidikan, 2023)
Interaction between lecturers and students is something that must be done to achieve the goals of the learning process. However, currently there are many media used to interact without meeting face to face. This article aims to analyze the role of WhatsApp groups as a medium for social interaction between lecturers and students. The research method used in this article is qualitative by collecting data through interviews with informants. The results of the interviews conducted show: 1) Whatsapp has an important role in conveying information when lectures cannot be conducted face to face, 2) Whatsapp as an interaction medium has the advantage of being able to convey information anywhere and at any time, while the disadvantage is interaction between Lecturers and Students face to face. directly limited, 3) The obstacle faced in using WhatsApp as a medium of interaction is that lecturers are less responsive.